Ireland : Sixth Review Under the Extended Arrangement: Staff Report; Staff Supplement; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2012)
The Sixth Review Under the Extended Arrangement with Ireland highlights that Ireland's policy implementation has continued to be steadfast. Ownership of the program remains strong despite the considerable challenges the country is facing. Ireland's progress in strengthening the financial system is reflected in the stability of the overall level of deposits in the banking system. Financial sector and structural reforms are advancing as envisaged. The authorities remain committed to achieving the 2012 fiscal targets and are developing a package of specific measures to further underpin the 2013-15 consolidation.